1992
DOI: 10.1042/bj2810297
|View full text |Cite
|
Sign up to set email alerts
|

Tetrahydrobiopterin-dependent formation of endothelium-derived relaxing factor (nitric oxide) in aortic endothelial cells

Abstract: Inhibition of tetrahydrobiopterin (H4biopterin) biosynthesis in endothelial cells almost completely abolished the agonist-induced formation of endothelium-derived relaxing factor (EDRF) (NO). This inhibitory effect could be antagonized when H4biopterin biosynthesis was restored by activating a salvage pathway. These data indicate that the formation of EDRF strictly depends on the presence of intracellular H4biopterin, which, in addition to Ca2+, may represent a further physiological and/or pathophysiological r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
0
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(73 citation statements)
references
References 30 publications
(30 reference statements)
3
69
0
1
Order By: Relevance
“…21 Thus, a deficiency of BH 4 produces two additive physiologic consequences: (a) uncoupling of the L-arginine NO pathway resulting in increased formation of oxygen-free radicals by eNOS 22 and (b) loss of NO production. 23 In a recent study, we found that deoxycorticosterone acetate salt hypertension caused BH 4 oxidation in aortas of mice, leading to a marked increase in superoxide production and a significant reduction in NO production. Treatment of these mice with oral BH 4 reduced vascular O 2 KÀ production, increased NO production and blunted the increase in BP due to deoxycorticosterone acetate salt hypertension.…”
Section: Potential Mechanismsmentioning
confidence: 92%
“…21 Thus, a deficiency of BH 4 produces two additive physiologic consequences: (a) uncoupling of the L-arginine NO pathway resulting in increased formation of oxygen-free radicals by eNOS 22 and (b) loss of NO production. 23 In a recent study, we found that deoxycorticosterone acetate salt hypertension caused BH 4 oxidation in aortas of mice, leading to a marked increase in superoxide production and a significant reduction in NO production. Treatment of these mice with oral BH 4 reduced vascular O 2 KÀ production, increased NO production and blunted the increase in BP due to deoxycorticosterone acetate salt hypertension.…”
Section: Potential Mechanismsmentioning
confidence: 92%
“…Fig. 8 shows that the 35 S-labeled band running at 135 kDa was specific for ecNOS and was not different between control and ascorbate-pretreated cells suggesting that ecNOS synthesis was not altered by ascorbic acid.…”
Section: Effect Of Ascorbic Acid On Ecnos Protein Content In Endothelmentioning
confidence: 94%
“…Medium 199 (M199), human serum, fetal calf serum, collagenase, and human serum albumin (HSA) were from Boehringer Ingelheim Bioproducts (Heidelberg, Germany). 35 S-label and methionine-free RPMI medium were from ICN Pharmaceuticals (Costa Mesa, CA); nitrocellulose was from Millipore (Eschborn, Germany); specific monoclonal antibodies against human ecNOS (clone 3) or against murine macrophage-inducible NOS (iNOS, clone 6) were from Transduction Laboratories (Lexington, KY); the fluorescein isothiocyanate-conjugated secondary antibody (rabbit anti-mouse IgG (H ϩ L)) with minimal cross-reaction to human serum proteins was from Dianova (Hamburg, Germany); NADPH, tetrahydrobiopterin, and L-nitroarginine methyl ester (L-NAME) were from Alexis Corp. (Lä ufelfingen, Switzerland). Endothelial cell growth supplement, peroxidase-labeled anti-mouse IgG (Fabspecific), anti-mouse agarose, FAD, FMN, calmodulin, ionomycin, thrombin, EDTA, EGTA, trypsin/EDTA solution (0.05/0.02%, v/v), leupeptin, phenylmethylsulfonyl fluoride (PMSF), L-ascorbic acid, dehydro-L-ascorbic acid, ascorbate 2-phosphate, ascorbate 2-sulfate, L-gulonolactone, and other reagents were purchased from Sigma (Deisenhofen, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, low levels of tetrahydrobiopterin (BH 4 ) were detected during the onset and progression of PD (2,16,17). BH 4 is a critical cofactor for NOS activity (18,19). Evidence indicates that BH 4 , by acting as a "redox switch," plays a critical role in increasing not only the rate of ⅐ NO generation by NOS, but also in controlling the formation of superoxide and hydrogen peroxide (20 -22).…”
mentioning
confidence: 99%